(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2024)
Independent tourism has grown rapidly with current technological advancements throughout generations of tourism. However, younger tourists make up a larger portion of this industry. The Independent Tourist era has presented new challenges and opportunities for the travel industry. It looks at how the expansion of travel alternatives in terms of destinations, modes of transportation, and activities due to the growth of digital platforms and easy access to information. Tourists can now make the best decisions for their preferences to the customization and personalization planning for their journey. This paper presents a conceptual paper, employing a systematic review methodology of the challenges and opportunities facing travel agencies amidst the era of independent tourism. Hence, the purpose of this paper is to enhance comprehension of this domain and identify potential gaps in existing literature pertaining to this subject matter. Based on the finding, most of the scholars support that travel agents must contend with growing competition, shifting consumer expectations, and altered value offerings because of these developments. It necessitates that travel agencies use technology to enhance their offerings while concentrating on offering specialized knowledge, customized travel package deals, and distinctive experiences for travel agencies at go above and beyond what is available to Free independent tourists. Travel agencies may find innovative ways to provide worthwhile experiences and exclusive access to places by collaborating with local partners, destination management organizations, and tour operators. Travel agencies can survive and thrive in a competitive travel market by embracing the era of independent travel and changing their business model.